Land Certification Information System of Sidoarjo Regency Land Office - Rizky Fajar Ryandi; Yulian Findawati (Universitas Muhammadiyah Sidoarjo, 2021)
The purpose of this research is to build land certification information system of Sidoarjo Regency Land Office. The information system is a form of development in making it easier for prospective applicants to make land easier and faster. To support the performance of employees of the Sidoarjo Regency Land Office and facilitate users in the manufacture of land certificates. In this research the method used is software development life cycle. The stage cycle contains requirement definition, system and software design, implementation and unit testing, intergration and system testing, operation and maintenance so that the implementation can be maximized. The result of this research has been built an information system based on Land Certification that greatly facilitates the performance of employees of the Sidoarjo Regency Land Office. Conclusion of research and discussion that Land Certification information system runs well and smoothly. With the land information system is expected to help the work of officers of the office of the national land agency, so that the efficiency and effectiveness of service performance can be improved and accelerate the service of officers to land-making transactions in Sidoarjo Regency. Respondents to the trial there were 3 people of Sidoarjo Regency and 7 officers of the Sidoarjo Regency Land Office. Data collection methods are carried out with interviews, literature studies and questionnaires. Based on the results of soil certification information system analysis, some aspects of PIECES analysis have obtained quite good results. One of them can be seen from the results of service category analysis, where the overall percentage of test questionnaires that have been shared, on average fall into the range of the category ''Very Easy